Characterization of 3-Oxacyl-Acyl Carrier Protein Reductase Homolog Genes in Pseudomonas aeruginosa PAO1 - Guo, Qiao-Qiao; Zhang, Wen-Bin; Zhang, Chao; Song, Yu-Lu; Liao, Yu-Ling; Ma, Jin-Cheng; Yu, Yong-Hong; Wang, Hai-Hong (Frontiers in Microbiology, 2019)
Bacterial 3-oxoacyl-ACP reductase (OAR) catalyzes the 3-oxoacyl-ACP reduction step in the fatty acid synthesis pathway. At least 12 genes in the Pseudomonas aeruginosa genome are annotated as OAR-encoding genes. In this study, we characterized the functions of these genes with biochemical and genetic techniques. With the exception of PA2697, which encodes FabG, an essential protein in fatty acid synthesis, only the PA4389 and PA4786 gene products had OAR activity, and the single deletion of these two genes reduced the ability of P. aeruginosa to produce several specific quorum-sensing (QS) signals. However, PA4389 and PA4786 do not play key roles in fatty acid synthesis. An analysis of carbon source utilization suggested that both OAR homologues predominantly function in sugar metabolism. Moreover, although most OAR homologues had no OAR activity, they may function in carbon utilization. The PA3128 product may play a role in the TCA cycle; PA2142 is involved in the catabolism of some sugars; and PA0182 and PA1470 seem to be required for the utilization of several amino acids. We conclude that most OAR homologue genes do not encode OAR enzymes, and proteins do not function in fatty acid synthesis.